Reversible complete heart block due to hypercalcaemia. Issue 1 (18th January 2021) - Ramakumar, Venkatakrishnan; Kothari, Shyam S; Seth, Sandeep; Kumar, Sumit
Abstract : A 65-year-old woman presented to the emergency room with a syncope. An ECG done revealed complete heart block with a narrow QRS escape rhythm and a normal QT interval. Further investigation revealed severe hypercalcaemia and elevated parathormone levels. Her heart block disappeared on correction of the hypercalcaemia. A right inferior parathyroid adenoma was found and surgically removed. Thus, hypercalcaemia may lead to reversible complete heart block without QT interval shortening.